The Influence of Environmental Conservation-Based Pop-Up Book Media on Elementary School Students' Awareness of Local Cultural Preservation - Hidayatullah, Farhan; Irawan, Roni; Irmaningsih, Irmaningsih (FKIP - Universitas Riau, 2025)
This study examines the impact of environmental conservation-based Pop-Up Book media on fifth-grade students’ awareness of local cultural preservation at SDN 07 Kota Bima. The background highlights students’ limited understanding and low concern for cultural and environmental issues, which are frequently associated with conventional teaching methods. The aim of this study is to evaluate the effectiveness of Pop-Up Book media in raising students’ awareness. A quantitative approach with a one-group pretest-posttest design was employed, involving 28 students selected through saturation sampling. Data were collected using tests, observations, and questionnaires, and analyzed using the Shapiro-Wilk normality test and Paired Samples t-test. The results indicated a significant improvement (p < 0.05) from the average pretest score of 31.89 (low category) to the posttest score of 76.43 (high category). Student evaluations averaged 4.47 (good to very good), while teacher evaluations averaged 4.78 (very good). These findings suggest that Pop-Up Book media not only enhance learning outcomes but also promote cultural and environmental awareness, making them an innovative and effective instructional medium for elementary education.